2014
DOI: 10.35197/rx.10.01.e.2014.14.ep
|View full text |Cite
|
Sign up to set email alerts
|

Uso de reptiles entre Yoremes y Yoris en el municipio de El Fuerte, Sinaloa

Abstract: De acuerdo con un estudio etnozoológico sobre el aprovechamiento de vertebrados silvestres en 11 comunidades Mayo-Yoreme del municipio de El Fuerte, Sinaloa, México, los reptiles fueron el tercer grupo el grupo de la etnofauna local más utilizados después de las aves y los mamíferos. Este trabajo tuvo como objetivo caracterizar y describir el uso de reptiles silvestres por Yoremes y Yoris (mestizos). El 58% de los usufructuarios se reconocieron como Yoremes, en tanto que el resto fueron Yoris. Se registraron n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Specifically, nuts and seeds, insects, and reptiles were present in literature reviews but were not reported by original studies, which might imply that they have become less representative of the TMexD over time. Indeed, the current consumption of nuts and seeds in Mexico is low [114,115], and insects and reptiles no longer form part of the usual diet, as these are only consumed as exotic foods [116] or in some southern or rural areas in Mexico [110,117,118,119]. In contrast, dairy and eggs were only mentioned in original studies, but not in literature reviews, which might imply that these foods were only recent inclusions to the Mexican diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, nuts and seeds, insects, and reptiles were present in literature reviews but were not reported by original studies, which might imply that they have become less representative of the TMexD over time. Indeed, the current consumption of nuts and seeds in Mexico is low [114,115], and insects and reptiles no longer form part of the usual diet, as these are only consumed as exotic foods [116] or in some southern or rural areas in Mexico [110,117,118,119]. In contrast, dairy and eggs were only mentioned in original studies, but not in literature reviews, which might imply that these foods were only recent inclusions to the Mexican diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, reptile consumption may no longer be as relevant in Mexico, especially if this diet was to be promoted in the general population. Reptiles were absent in all studies combined and those describing all geographical regions, and their commercialisation (i.e., turtles, iguanas, and snakes) is prohibited in order to preserve the species [117,120,121].…”
Section: Discussionmentioning
confidence: 99%
“…También se han reportado usos medicinales de las víboras de cascabel para otras regiones de Chiapas (Barrasa-García, 2015), Oaxaca (Buenrostro-Silva et al, 2016), Veracruz (Gómez-Landa, 2015), Ciudad de México (Gómez-Álvarez & Pacheco-Coronel, 2010), Puebla (Cossío-Bayugar, 2007) y Guanajuato (Leyte-Manrique et al, 2016). Esta especie se usa con fines ornamentales y comerciales en Morelos (Reyna-Rojas et al, 2015) y alimenticios en el estado de México (Monroy-Vilchis et al, 2016) y Sinaloa (Pascual-Ramos et al, 2014). Por su parte, para las especies del género Micrurus sólo ocasionalmente se menciona su uso con fines medicinales en la parte central de la Altiplanicie de Chiapas (Enríquez et al, 2006) y Sinaloa (Pascual-Ramos et al, 2014).…”
Section: Discussionunclassified
“…Esta especie se usa con fines ornamentales y comerciales en Morelos (Reyna-Rojas et al, 2015) y alimenticios en el estado de México (Monroy-Vilchis et al, 2016) y Sinaloa (Pascual-Ramos et al, 2014). Por su parte, para las especies del género Micrurus sólo ocasionalmente se menciona su uso con fines medicinales en la parte central de la Altiplanicie de Chiapas (Enríquez et al, 2006) y Sinaloa (Pascual-Ramos et al, 2014).…”
Section: Discussionunclassified
“…Los distintos pueblos originarios de México han demostrado una estrecha relación con los recursos naturales, como se ha podido apreciar a partir de los estudios realizados en diversos grupos, tales como los indígenas tlahuicas (Guerrero y Retana, 2015), la comunidad mazahua (Sánchez Núñez, 2006) o los yoremes y yoris (Pascual et al, 2014), entre muchos otros. En el estado de Yucatán, la cultura maya ha demostrado estar estrechamente relacionada con la naturaleza y, ya sea por necesidad o tradición, aún mantiene un fuerte aprovechamiento de los recursos faunísticos en la región (Chablé y Delfín, 2010).…”
Section: Introductionunclassified